Application of Ohmic Heating Method as an Alternative Technology for Beverage Processing - Rabbani, Salma Salsabila; Listanti, Riana (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2025)
Background: Ohmic heating is an alternative thermal heating that can be used in beverage product processing. The working principle of the ohmic heating method is by flowing an alternating electric current through the beverage product and causing ions to move towards electrodes with opposite charges so that the product has an even internal heat. Purpose: This study aims to analyze the influence and potential emission, advantages and challenges regarding the use of the ohmic heating method and its future applications. Method: This paper summarizes the effect of ohmic heating on beverage products during 2015-2025. This study uses variables in the form of voltage and frequency variations applied to various types of processed beverage products. In ohmic heating performance, voltage and frequency variations play a very important role in beverage processing. Results: The results show that the use of ohmic heating methods in beverage product processing has low energy consumption, even (homogeneous) heat, short time, increased product safety and quality. The ohmic heating method affects the properties of beverage products. Differences in process objectives in the use of beverage products such as boiling, cooking, pasteurization, microbiological inactivation, sterilization can also affect the level of product quality and safety so that knowledge is needed regarding the application of the right temperature, frequency, voltage and time according to the type and purpose of processed beverage products. However, the application of ohmic heating methods still faces many obstacles, such as high costs that limit its commercial use at a larger scale. Furthermore, most research is still conducted at the laboratory and pilot scale, with very little research at the factory scale. Therefore, more research is needed into large-scale ohmic heating applications to evaluate potential technical and economic challenges.